Analisis Penerapan Etika Bisnis Islam Terhadap Pedagang di Kawasan Wisata Religi Makam Gus Dur Jombang - Alfina Rahmadaniar; Abdur Rohman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out the mechanism for implementing Islamic business ethics among traders in the Gus Dur Tomb religious tourism area, Jombang. This research uses a qualitative descriptive approach with direct observation and in-depth interviews. Data was collected through observation, interviews with traders, and literature study. The research results show that many traders in the region do not fully understand and apply the principles of Islamic business ethics in their trading activities. Unhealthy trading practices that are not in accordance with sharia are still found, even in religious tourism areas. This research suggests the need for education and outreach regarding Islamic business ethics to traders to create a market environment that is fairer and in accordance with Islamic principles.